Synthesis and Characterization of Nickel Cobalt Vanadate (NiCo2V2O8) Nanostructures: Photocatalytic and Supercapacitor Applications - Naik R., Lakshmana; Bala Narsaiah, T.; Ravikumar, C.R.; Naveen Kumar, A.; Vinutha, K.; Jahagirdar, A.A.; Ananda Murthy, H.C. (Asian Journal of Chemistry, 2021)
With the emerging newer energy storage applications, transition metal vanadates are booming up as better catalysts. Among all the transition metal vanadates, nickel cobalt vanadate nanomaterials (NiCo2V2O8 NP), are being considered as a promising material with electrocatalytic and photocatalytic activity. In this article, the synthesis of circular and ovular structured NiCo2V2O8 nanostructures by the hydrothermal route without using any capping agent is reported. The crystallinity, physical structure and morphology of the prepared nanomaterial were studied by X-ray diffraction (XRD), transmission electron microscopy (TEM) and Fourier transform infrared (FT-IR) spectroscopy. The photocatalytic property of NiCo2V2O8 nanostructures was studied by decolorizing industrially hazardous dye such as malachite green dye under ultra-violet light conditions for a regular interval of time (10 min) up to 60 min. The experiments showed decolorization efficiencies as 52.43 for malachite green dye. The electrochemical behaviour of the prepared compound was studied and energy specific capacity was elucidated as 218.4 F g-1 with high reversibility property the material. The NiCo2V2O8 nanostructures showed better electrochemical activity and photocatalytic activity, which could be utilized for supercapacitor and pollutant remediation applications.